Observation of rotation about the longest principal axis in Zr 89 - Saha, S.; Palit, R.; Sethi, J.; Biswas, S.; Singh, P.; Nag, S.; Singh, A.K.; Ragnarsson, I.; Babra, F.S.; Garg, U.; Goswami, A.; Ideguchi, E.; et al. (American Physical Society, 2020)
High-spin states in Zr89 were populated in the Se80(C13,4n) reaction, and γ-ray coincidences were measured using the Indian National Gamma Array. The level scheme of Zr89 has been extended up to spin I=49/2 with the observation of a new dipole band. Directional correlation and polarization asymmetries of the γ rays have been measured to determine spin and parity of the levels. Line shapes of several transitions have been analyzed to determine lifetimes of the levels. Possible configurations of the band have been discussed using the cranked Nilsson-Strutinsky model. The calculations suggest a triaxial shape of the nucleus at high spins, and the band may represent rotation of the nucleus about the longest axis. © 2019 American Physical Society.